O efeito da codificação da desnutrição no financiamento hospitalar - Coelho, Alexandra (2012)
Introduct ion: Disease-related undernutrition is a health care concern which remains under -recognized and under -treated. The absence of routine screening at hospital admission is one of the main reasons for this perennial problem. In order to implement undernutrition screening and nutritional treatment, it is important to evaluate the economic impact of undernutrition documentation held in medicai records. Aim: To assess the financiai benefits of systematically screening and assessing patients at hospital admission and their documentation in clinicai notes. Met hods: Systematic screening and diagnosis of undernutrition in patients consecutively admitted in oncology and multidisciplinary departments of an oncology hospital was performed using the Patient -Generated Subjective Global Assessment. The diagnosis of undernutrition was documented in the clinicai process and was considered for the codification of Diagnosis Related Groups (DRG). A test including undernutrition co-morbidity was carried out. Relative weight and price of DRGs with and without undernutrition were assessed. Result s: Forty-seven patients were evaluated, of those, 23 (48.9%) were undernourished. Only three of the aforementioned patients accounted for an increase in total hospital funding which came to €9,006. (onclusions: The documentation of undernutrition in the clinicai record had a relevant economic impact. This justified the resources implicated in the practice of routine screening of undernutrition and nutritional therapy with the aim of improving nutritional status in hospital patients.